2020
DOI: 10.1016/j.bbagrm.2020.194507
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear accumulation of MKL1 in luminal breast cancer cells impairs genomic activity of ERα and is associated with endocrine resistance

Abstract: Estrogen receptor (ERα) is central in driving the development of hormone-dependent breast cancers. A major challenge in treating these cancers is to understand and overcome endocrine resistance. The Megakaryoblastic Leukemia 1 (MKL1, MRTFA) protein is a master regulator of actin dynamic and cellular motile functions, whose nuclear translocation favors epithelial-mesenchymal transition. We previously demonstrated that nuclear accumulation of MKL1 in estrogen-responsive breast cancer cell lines promotes hormonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 59 publications
3
20
0
Order By: Relevance
“…(iii) Our work analyzed just the final state after 48 h of the induction of MKL1 variants expression. However, the results we present here supported by the use of two different control cells, together with the studies reported in Jehanno and Fernández-Calero et al [29], allow us to validate the current cell model to deepen studies on EMT processes.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…(iii) Our work analyzed just the final state after 48 h of the induction of MKL1 variants expression. However, the results we present here supported by the use of two different control cells, together with the studies reported in Jehanno and Fernández-Calero et al [29], allow us to validate the current cell model to deepen studies on EMT processes.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, a number of genes involved in kinase cascades and signal transduction are upregulated, consistent with the induction of an EM-like transition [30]. We also found an underrepresentation of genes involved in epigenetic marks such as chromatin remodeling and DNA methylation, which indicates cell cycle arrest, consistent with the induction of an EM-like transition (reviewed in [29,30]).…”
Section: Differentially Expressed Genes Validate the Induction Of An supporting
confidence: 72%
See 3 more Smart Citations